Práticas de marketing e endomarketing para bibliotecas universitárias - Moreira, Elaine Cristina de Brito (2014)
The current study investigates the marketing and endomarketing practices applied in the university libraries having the general objective to analyze the best marketing and endomarketing practices adopted by the university libraries in the scientific production of the National Seminar of University Libraries (SNBU) event, between 2008 and 2013. It is a descriptive-exploratory and bibliographical piece of research with quantitative and qualitative approach. It adopts the scientometry, a research tool that enables diagnosing the practices. In order to analyze data, it uses the research field, by means of scientific production existent in the Librarianship and Documentation conference proceedings, in which it was possible to collect the marketing and endomarketing practices. The obtained results allowed identifying the practices adopted in the university libraries; this provided the understanding in regard to the use of practices suggested by the literature as the best way to attract and please clients. In addition to this, the results highlighted that the university libraries are ready to cater to and please their clients, always seeking the technological innovation and the market competitiveness so as to become an active organism in society. The librarian, information manager and mediator, is aware of his or her role in the information society. It can be concluded that the marketing and endomarketing techniques, in which the practices are well defined and structured, by using the benchmarking, may lead the university library to conquer its place in society as well as to attain competitiveness in the present market and in the organizational environment.